Ophiocephalus striatus Extract Supplementation Decreases Serum IL-6 Levels in Older People with Sarcopenia—A Single-Center Experience - Nur Riviati; Legiran Legiran; Irsan Saleh; Taufik Indrajaya; Zulkhair Ali; Irfannuddin; Probosuseno (Geriatrics, 2024)
Sarcopenia, a condition characterized by muscle loss and decreased function in older adults, is a growing public health concern. This study aimed to investigate the effects of Ophiocephalus striatus extract on insulin-like growth factor-1 serum, interleukin-6 serum levels, and sarcopenia-related parameters in older adults with sarcopenia. This double-blind randomized controlled trial included 80 older adults with sarcopenia. Participants were randomly assigned to receive Ophiocephalus striatus extract or a placebo for two weeks. The IGF-1 serum and IL-6 serum levels were assessed as primary outcomes. The Ophiocephalus striatus extract intervention resulted in a significant reduction in serum IL-6 levels. Although the IGF-1 levels did not show significant changes, there was an increase for the intervention group. This study demonstrated that a 2-week intervention with Ophiocephalus striatus extract positively impacted the serum IL-6 levels in older adults with sarcopenia. While the IGF-1 levels did not change significantly in this short intervention period, the observed improvements in IGF-1, calf circumference, muscle mass, and muscle strength are promising. The findings suggest that Ophiocephalus striatus extract may offer a valuable intervention for managing sarcopenia, particularly in regions with abundant Ophiocephalus striatus production, such as South Sumatera. This study was registered with trial number NCT05869383.